SISTEM INFORMASI MANAJEMEN (SIM) DI ERA DIGITAL: TREN BARU, IMPLEMENTASI, DAN TANTANGAN DI INDONESIA - Samosir, Yosafat Renovaldo; Jhon Kristopel Manalu; Darwis Manalu (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The advancement of the digital era has significantly driven organizational transformation through the implementation of Management Information Systems (MIS). This article aims to comprehensively review the latest trends in MIS, its implementation in Indonesia, and the challenges encountered. Employing an exploratory literature study approach with a descriptive design, data were collected from primary sources such as government reports and company documents, and secondary sources including indexed scientific journals and professional publications from the 2021-2026 period. Content analysis was used to systematically identify and present the findings. The results indicate that modern MIS trends are dominated by the integration of Artificial Intelligence (AI) and Machine Learning (ML), the adoption of cloud-based solutions, the utilization of big data analytics, and the strengthening of information security. Implementation in Indonesia, examined through case studies in the healthcare and business sectors, demonstrates the potential to improve service quality and operational efficiency. However, various challenges persist, such as low user discipline, infrastructure limitations, weak system integration, and data protection issues. This article concludes that successful MIS implementation requires a holistic approach encompassing the enhancement of human resource competence, strengthening of technological infrastructure, and sustained policy support. Reference management tools like Mendeley also play a crucial role in supporting research productivity and academic writing.